The roles of binge gaming in social, academic and mental health outcomes and gender differences: A school-based survey in Hong Kong - Nick Tse; Natalie Sze Nga Pang; Xin Wang; Yiran Li; Camilla Kin Ming Lo; Xue Yang (PLoS ONE, 2025)
Binge gaming, defined as playing video games for more than five consecutive hours, has become an emerging health and behavioral issue among children and adolescents. However, the potential factors and consequences have not been sufficiently investigated. This study aims to examine the prevalence of binge gaming, its social, academic, and mental health consequences, and potential gender differences among children and adolescents in Hong Kong. A school-based survey was conducted on 2,592 primary and secondary students in Hong Kong. The sample included 1,404 boys (mean age = 11.99 + /- 2.415 years) and 1,188 girls (mean age = 11.77 + /- 2.473 years), with an overall mean age of 11.89 years. Internet gaming disorder (IGD), depression, anxiety, stress, loneliness, social support, sleep quality, and educational self-efficacy were measured using well-validated self-report scales. Analysis of Covariance (ANCOVA) models, adjusting for age and daily gaming time, were employed to examine mental, social, and academic outcomes among binge gamers, non-binge gamers, and non-gamers. Subgroup analyses were conducted by gender. The overall prevalence of binge gaming in the study sample was 31.7%. Thirty percent of respondents reported at least one episode of binge gaming in the last month, with 38.3% in boys and 24.0% in girls. In boys, binge gamers showed greater IGD, depression, anxiety, and stress, poorer sleep quality, and lower educational self-efficacy than non-binge gamers. Similarly, female binge gamers exhibited higher IGD, depression, anxiety, stress, and loneliness, and lower educational self-efficacy, sleep quality, and social support. Non-gamers generally experienced less depression, anxiety, stress, and loneliness, and higher educational self-efficacy, than binge gamers in both genders. Binge gaming may act as a behavioral indicator and risk factor for various social, academic, and health problems and preventive effort is warranted.